Transseptal transcatheter mitral valve replacement - V. I. Ganyukov; R. S. Tarasov; I. V. Ganyukov (Российский кардиологический журнал)
The review presents current data transseptal transcatheter mitral valve replacement, which is becoming an alternative method of managing mitral valve disease. Despite the fact that the transapical transcatheter approach is technically simpler, the transseptal method is less invasive. It has confirmed effectiveness and is predicted to be the most promising. The review describes the relevance, indications, methodology for selecting the required endoprosthesis, stages of procedure, complications, and the postoperative follow-up of patients. The results of publications on transseptal transcatheter mitral valve replacement are analyzed. A case report is given.